2017
DOI: 10.1016/j.drudis.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting receptor tyrosine kinase co-activation for cancer therapy

Abstract: Studies over the past decade have shown that Receptor Tyrosine Kinase (RTK) co-activation is prevalent in many cancer types. Compelling data demonstrates that cancers are likely to have evolved RTK co-activation as a generic means for driving tumour growth and providing a buffering system to limit the lethal effects of microenvironmental insults including therapy. In this review, we summarise the general principles of RTK co-activation gleaned from key studies over the last decade. We discuss direct and indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 108 publications
0
27
0
Order By: Relevance
“…Subsequently, Akt is activated and phosphorylates specific downstream proteins, including the pro-apoptotic proteins of the Bcl-2 family and glycogen synthase kinase 3 (GSK-3), thereby preventing the phosphorylation and degradation of cyclin D1 (33). Several RTKs regulate the activation of the PI3K/Akt pathway (34). It has been reported that, by inhibiting the activity of PI3K, cell proliferation may be significantly reduced and cell cycle progression prohibited; however, these effects may be prevented when activated Akt (p-Akt) is expressed (32).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Akt is activated and phosphorylates specific downstream proteins, including the pro-apoptotic proteins of the Bcl-2 family and glycogen synthase kinase 3 (GSK-3), thereby preventing the phosphorylation and degradation of cyclin D1 (33). Several RTKs regulate the activation of the PI3K/Akt pathway (34). It has been reported that, by inhibiting the activity of PI3K, cell proliferation may be significantly reduced and cell cycle progression prohibited; however, these effects may be prevented when activated Akt (p-Akt) is expressed (32).…”
Section: Discussionmentioning
confidence: 99%
“…Our study presents one mechanism of acquired resistance to pazopanib in soft tissue malignancies through PDGFRα loss and bypass of the AKT-signaling pathway, and it provides a means to overcome this resistance via FGFR1 blockade in vitro. Since it is less likely for cancer cells to develop acquired resistance when multiple RTKs are simultaneously inhibited up front, there is a rationale for using the PDGFRα and FGFR1 inhibitor combination as first-line therapy (Tan et al., 2016). Indeed, attempts by our laboratory to generate acquired resistant lines to the PDGFRα and FGFR inhibitor combination have been unsuccessful (Figure S2H).…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Xu et al demonstrated that the receptor tyrosine kinase (RTK) coactivation network was an important mechanism promoting tumor development and limiting the lethal effects of targeted drugs (Xu and Huang 2010). Therefore, aiming to determine the individual signaling pathway of an RTK is no longer appropriate, and targeting the downstream pathways of RTKs has become a new strategy to solve this issue (Tan et al 2017). RICTOR, the core component of the PI3K/Akt pathway, has been shown to be involved in tumor survival and drug resistance.…”
Section: Discussionmentioning
confidence: 99%